The “save the earth!” narrative creates a narrative trap for climate advocates - Laird, Frank N. (Frontiers in Climate, 2022)
The phrase “Save the Earth!” encapsulates a common narrative among climate advocates, one of environmentalists battling polluters to save Mother Earth from being despoiled. In this narrative the moral boundaries are clear and the stakes are apocalyptic, leaving no room for doubt or compromise. Nonetheless, the narrative has not been an effective one for climate activists. Most importantly, it does not lay out a path for overcoming the deeply institutionalized barriers to transforming a large sociotechnical system. Climate advocates need a new narrative, one that continues to stress decarbonizing the economy but also emphasizes adapting to climate change that is already in the pipeline and ensuring a just transition that does not harm the most vulnerable parts of the population nor frustrate the aspirations of people around the world who seek better lives for themselves. The burgeoning field of just energy transitions encompasses these concerns, but it too needs a new story, one that avoids the narrative traps that have hampered climate policy more generally.